Microstructure Analysis on Friction Stir Welding of Magnesium Alloys - Manikandan, J.; Ramanjaneyulu, D. Surya (International Journal of Psychosocial Rehabilitation, 2019)
Friction stir welding is an eco-friendly solid-state welding technique employed particularly for joining the magnesium alloys since it is a light-weight metal that is difficult to join by conventional processes. During the friction stir welding process, the influence of tool rotational speed on the magnesium alloy is carried out at different speeds. Further microstructure analysis is performed on the welded joint; from this we find microstructure evolution, weld defects and properties of weld tool